Rusya’nın Kafkasya siyaseti : General Paskeviç’in başkomutanlığı dönemi (1827-1831) - Çaycığlu, Serdar Oğuzhan (My University, 2018)
Bu çalışmada, 1827-1831 yılları arasında Müstakil Kafkasya Kolordusu Başkomutanlığı görevinde bulunan General İvan Fyodoroviç Paskeviç’in askeri faaliyetleri üzerinden Rusya’nın Kafkasya siyaseti ele alınmıştır.

In this research, the Caucasian politics of Russians were discussed through the military activities of General Ivan Fyodorovich Paskevich, who served as the military Commander-in-Chief of the Caucasia between 1827 and 1831.
Keywords: 1826-1828 Russian –Iranian War; 1826-1828 Rusya-İran Savaşı; 1828-1829 Osmanlı-Rus Savaşı; 1828-1829 Ottoman – Russian War; Caucasus; Dış ilişkiler; Foreign relations; History; İlişkiler; İlişkileri; Kafkasya; Paskevich; Paskeviç; Relations; Russia; Rusy; Rusya; Tarih; Turkey; Turkiye; Türkiye